Exploration and Reflection on Mental Health Education of College Students in China - Ding, Xiaosheng (Advances in Social Sciences Research Journal, 2016)
Mental health education is an important carrier of university personnel training and a significant component of ideological and political education. In order to launch the mental health education work in a solid way, the work aims at free and all-round development of college students, combined with his long-term work practice. It is suggested to start with the goal, principle and approach of mental health education, so as to promote the harmony and healthy development of college students.